PELATIHAN PEMBUATAN VIDEO AJAR ONLINE MENGGUNAKAN KINEMASTER - Nova Jayanti Harahap (PT.JNDI, JURNAL BIMA, 2024)
The teaching and learning process at the university level is currently not only carried out offline but also online. Some lecturers at universities still have difficulty in creating interesting learning using applications due to limited expertise and sufficient knowledge. Through this service, training will be provided using the kinemaster application for video editing and creating interesting teaching materials on mobile phones and laptops. This service is based on the shortcomings or lack of student interest in monotonous online learning, so with changes in the appearance of interesting teaching materials, students and lecturers can be more active and enthusiastic in the teaching and learning process. To achieve maximum goals, the author identifies problems, determines objectives, activity plans, carries out training and evaluations. The service was attended by 12 participants, carried out online through meetings using the google meet application. The enthusiasm of the service participants was very good, seen from the results of the questionnaire which reached 78% of participants stating that the content of the training material was good, 4 participants thought the delivery of the material was satisfactory and according to needs.